2013
DOI: 10.1590/s0102-05362013000300014
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência do silicato de potássio no controle do oídio e no desenvolvimento de abobrinha de moita

Abstract: A medida mais utilizada para o controle de oídio em cucurbitáceas é o uso de variedades resistentes e fungicidas sistêmicos, entretanto, a nutrição silicatada tem se mostrado uma opção. O fornecimento do silício é benéfico para muitas espécies vegetais, estimulando o crescimento, a produção, a fotossíntese e a regulação da transpiração; além disso, sua deposição na epiderme evita a invasão de fungos, bactérias e insetos sugadores. O objetivo deste trabalho foi verificar a influência do silicato de potássio no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Comparing the highest total production (2.2 kg plant -1 ) and commercial (1.9 kg plant -1 ) obtained in this work with other researches, these were superior to those reported by Ramos et al (2013), with 1.3 and 1.1 kg plant -1 in total and commercial fruit production, respectively, using the Caserta cultivar. Pôrto et al (2014), with the same cultivar, obtained total production of 1.79 kg plant -1 in the dose 331 kg ha -1 of N, dose higher than those studied in this study.…”
Section: Experiments 2 (2015)contrasting
confidence: 70%
“…Comparing the highest total production (2.2 kg plant -1 ) and commercial (1.9 kg plant -1 ) obtained in this work with other researches, these were superior to those reported by Ramos et al (2013), with 1.3 and 1.1 kg plant -1 in total and commercial fruit production, respectively, using the Caserta cultivar. Pôrto et al (2014), with the same cultivar, obtained total production of 1.79 kg plant -1 in the dose 331 kg ha -1 of N, dose higher than those studied in this study.…”
Section: Experiments 2 (2015)contrasting
confidence: 70%
“…Rodrigues et al (2015a) reported no signifi cant alterations in the values of C i , g s , and E for common bean plants sprayed with PS, but a signifi cant reduction on anthracnose severity and an increase on yield were achieved. According to Ramos et al (2013), the high rates of diff erent Si sources used to control powdery mildew on pumpkin plants should be taken into account since leaf gas exchange parameters and yield may be aff ected. Interestingly, the combination of PS with fungicide caused an adverse eff ect on the photosynthetic performance of wheat plants in this study.…”
Section: Foliar Application Of Silicon Decreases Wheat Blast Symptoms Without Impairing Photosynthesismentioning
confidence: 99%
“…Some studies present the element as an alternative to disease control in different pathosystems (Mendonça et al, 2013;Ramos et al, 2013;Santos et al, 2014), including the root-knot nematode (Dutra, 2004;Guimarães et al, 2008;Oliveira et al, 2012), in which *Corresponding author. E-mail: dani.mattei@hotmail.com.…”
Section: Introductionmentioning
confidence: 99%